The Effect of Fasting on Health of Stomach Digestion System - Masyitoh Masyitoh Masyitoh; Amelia Novita; Muhammad Farid; Andriyani Asmuni; Suherman Suherman; Munaya Fauziah; Najwa Khairina; Dina Rahma Fadlilah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
The human body has important digestive organs such as the stomach. One of the stomach diseases that is gastritis or ulcers has indeed begun to be experienced due to a lack of knowledge about the factors that cause gastritis and behavior to prevent the occurrence of gastritis. Gastritis known as ulcer disease is an inflammation or bleeding in the mucosa of the stomach caused by irritants, infections, and irregularities in the diet. The method used is a literature review article by reviewing 7 journals published from 2010-2020 about the effect of fasting on the health of the stomach digestive system conducted in April 2020. The results of changing dietary patterns during fasting cause various changes in the body, especially in the digestive tract. Fasting gives the digestive system time to rest, so it can reduce the risk or cure health problems indigestion. The conclusion is that there is a relationship between diet, knowledge, and stress to the incidence of gastritis. While in the behavior of coffee consumption and sex there is no association with the incidence of gastritis.